2023
DOI: 10.1186/s13287-023-03520-3
|View full text |Cite
|
Sign up to set email alerts
|

Advances in stem cell therapy for peritoneal fibrosis: from mechanisms to therapeutics

Weiyan Huang,
Demeng Xia,
Wendi Bi
et al.

Abstract: Peritoneal fibrosis (PF) is a pathophysiological condition caused by a variety of pathogenic factors. The most important features of PF are mesothelial–mesenchymal transition and accumulation of activated (myo-)fibroblasts, which hinder effective treatment; thus, it is critical to identify other practical approaches. Recently, stem cell (SC) therapy has been indicated to be a potential strategy for this disease. Increasing evidence suggests that many kinds of SCs alleviate PF mainly by differentiating into mes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 131 publications
0
5
0
Order By: Relevance
“…Stem cells (SCs) can differentiate into any cell of the human body and are responsible for the development and regeneration of organs and tissues. SCs may influence cellular differentiation and exert immune regulation and cellular repair effects [ 115 ], and their therapeutic potential has been investigated in several pathologies including peritoneal inflammation and fibrosis, mesenchymal SCs (MSCs) being the most extensively studied [ 116 ]. In vitro and in vivo studies showed that MSCs might represent a novel and effective treatment of PF, mainly through paracrine activity to accelerate healing or differentiation into functional repair cells [ 115 ].…”
Section: Combating Pd-solution Associated Toxicitymentioning
confidence: 99%
See 2 more Smart Citations
“…Stem cells (SCs) can differentiate into any cell of the human body and are responsible for the development and regeneration of organs and tissues. SCs may influence cellular differentiation and exert immune regulation and cellular repair effects [ 115 ], and their therapeutic potential has been investigated in several pathologies including peritoneal inflammation and fibrosis, mesenchymal SCs (MSCs) being the most extensively studied [ 116 ]. In vitro and in vivo studies showed that MSCs might represent a novel and effective treatment of PF, mainly through paracrine activity to accelerate healing or differentiation into functional repair cells [ 115 ].…”
Section: Combating Pd-solution Associated Toxicitymentioning
confidence: 99%
“…SCs may influence cellular differentiation and exert immune regulation and cellular repair effects [ 115 ], and their therapeutic potential has been investigated in several pathologies including peritoneal inflammation and fibrosis, mesenchymal SCs (MSCs) being the most extensively studied [ 116 ]. In vitro and in vivo studies showed that MSCs might represent a novel and effective treatment of PF, mainly through paracrine activity to accelerate healing or differentiation into functional repair cells [ 115 ]. In a uremic rat PF model, intravenous injection of adipose-derived MSCs displayed anti-inflammatory (avoidance of leukocyte infiltration and overexpression of inflammatory cytokines including IL-1, IL-6, and TNF-alpha) and anti-fibrotic (regulation of TGF-beta, collagen, and fibronectin) effects in the PM [ 117 ].…”
Section: Combating Pd-solution Associated Toxicitymentioning
confidence: 99%
See 1 more Smart Citation
“…These changes impair the function of the PM as a dialysis membrane. Mesothelial–mesenchymal transition (MMT) is a key mechanism that contributes to development of PF by generating fibroblasts and myofibroblasts from PMCs ( Huang et al, 2023 ). MMT is a physiological process that generates fibroblasts and related cells from mesothelial cells to repair damaged tissues.…”
Section: Introductionmentioning
confidence: 99%
“…This process is normally self-limiting and stops when the injury is resolved. However, under persistent stimuli, MMT can become pathological and lead to excessive fibroblast proliferation and tissue fibrosis ( Huang et al, 2023 ). TGF-β1 is involved in the differentiation of PMFBs of resident fibroblasts and also in the mesenchymal conversion of endothelial cells via endothelial-to-mesenchymal transition (EnMT), which call forth to target vasculopathy for the abrogation of fibrosis ( Zeisberg et al, 2007 ; Zeisberg et al, 2008 ; Li et al, 2009 ; Beyer et al, 2012 ).…”
Section: Introductionmentioning
confidence: 99%